1990
DOI: 10.1182/blood.v76.12.2565.2565
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leukocyte alkaline phosphatase gene in normal and leukemic cells: regulation of the transcript by granulocyte colony- stimulating factor

Abstract: The levels of leukocyte alkaline phosphatase (LAP) messenger RNA (mRNA) are evaluated in B and T lymphocytes, monocytes, and polymorphonuclear cells (PMNs), and this transcript is found to be present only in PMNs. Precursors of the myelomonocytic pathway, represented by leukemic cells isolated from several cases of chronic myelogenous leukemia (CML) in its stable and blastic phase and acute myelogenous leukemia (AML), are devoid of LAP transcript. These data support the notion that LAP is a marker of the granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In addition, although the function of LAP is not yet known, the presence of mature granulocytes negative for the expression of both the surface and the cytoplasmic form of the protein, suggests that in normal myeloid differentiation LAP does not play a necessary role in the release of mature granulocytes from the bone morrow into the blood stream. We and others previously showed that G-CSF regulates LAP mRNA expression in normal and CML granulocytes (Rambaldi et al, 1989(Rambaldi et al, , 1990Sato et al, 1991). In this study we have provided evidence that pharmacological doses of G-CSF increase in vitro the cell surface expression of LAP protein in normal granulocytes.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In addition, although the function of LAP is not yet known, the presence of mature granulocytes negative for the expression of both the surface and the cytoplasmic form of the protein, suggests that in normal myeloid differentiation LAP does not play a necessary role in the release of mature granulocytes from the bone morrow into the blood stream. We and others previously showed that G-CSF regulates LAP mRNA expression in normal and CML granulocytes (Rambaldi et al, 1989(Rambaldi et al, , 1990Sato et al, 1991). In this study we have provided evidence that pharmacological doses of G-CSF increase in vitro the cell surface expression of LAP protein in normal granulocytes.…”
Section: Discussionsupporting
confidence: 63%
“…Short-term incubation (2-6 h) was not associated with modification in the fluorescence profile of 1B12.1 MoAb as compared to control samples (data not shown). Not surprisingly, this G-CSF-mediated up-regulation of LAP surface expression occurred in parallel with a concomitant modulation of apoptosis (Rambaldi et al, 1990;Sato et al, 1991;De Renzo et al, 1990;Colotta et al, 1992;Homburg et al, 1995). In fact, as determined by the annexin V assay, we found that only 20% of normal granulocytes cultured for 24 h with G-CSF showed an apoptotic phenotype as compared to 40% of granulocytes cultured in medium alone (data not shown).…”
Section: G-csf Induces the Lap Cell Surface Expression In Normal And mentioning
confidence: 70%
See 3 more Smart Citations